Focused time-lapse analysis reveals novel aspects of human fertilization and suggests new parameters of embryo viability. Issue 1 (15th November 2017) - Coticchio, G; Mignini Renzini, M; Novara, P V; Lain, M; De Ponti, E; Turchi, D; Fadini, R; Dal Canto, M
Abstract: STUDY QUESTION: Can focused application of time-lapse microscopy (TLM) lead to a more detailed map of the morphokinetics of human fertilization, revealing novel or neglected aspects of this process? SUMMARY ANSWER: Intensive harnessing of TLM reveals novel or previously poorly characterised phenomena of fertilization, such as a cytoplasmic wave (CW) preceding pronuclear formation and kinetics of pronuclear chromatin polarization, thereby suggesting novel non-invasive biomarkers of embryo quality. WHAT IS KNOWN ALREADY: In recent years, human preimplantation development has been the object of TLM studies with the intent to develop morphokinetic algorithms able to predict blastocyst formation and implantation. Regardless, our appreciation of the morphokinetics of fertilization remains rather scarce, currently including only times of polar body II (PBII) emission, pronuclear appearance and fading, and first cleavage. This is not consistent with the complexity and importance of this process, calling for further TLM studies aimed at describing previously unrecognized or undetected morphokinetic events and identifying novel developmental biomarkers. STUDY DESIGN, SIZE, DURATION: The study involved a retrospective observation by TLM of the fertilization process in 500 oocytes utilized in consecutive ICSI cycles carried out in 2016. A maximum of five fertilized oocytes per patients were included in the analysis to reduce possible patient-specific biases. Oocytes of patients with different diagnoses of infertility where included in the analysis, while cases involving cryopreserved gametes or surgically retrieved sperm were excluded. PARTICIPANTS/MATERIALS, SETTINGS, METHODS: Microinjected oocytes where assessed by a combined TLM-culture system (Embryoscope). Oocytes that were not amenable to TLM assessment, due to excess of residual corona cells or inadequate orientation for the observation of PBII emission, were not analysed. We identified and monitored 28 parameters relevant to meiotic resumption, pronuclear dynamics, chromatin organization, and cytoplasmic/cortical modifications. Times (T) were expressed as mean ± SD hours post-insemination (p.i.) and analysed, where appropriate, by Paired T Student or Fisher's exact tests. MAIN RESULTS AND ROLE OF CHANCE: PBII emission was occasionally followed (4.3% of cases) by the transient appearance of a protrusion of the cell surface, the fertilization cone (FC), probably resulting from interaction of the male chromatin with the oocyte cortex. Pronuclear formation was always preceded by a radial CW originating from the initial position of the male pronucleus (PN) and extending towards the oocyte periphery. The appearance of the CW followed a precise sequence, occurring always 2–3 h after PBII emission and shortly before PN appearance. Male and female PN appeared virtually simultaneously at approximately 6.2 h p.i. However, while the female PN always formed cortically and near the site of emission of the PBII, the initial position of the male PN was cortical, intermediate, or central (15.2%, 31.2% and 53.6%, respectively). PN juxtaposition involved rapid and straight movement of the female PN towards the male PN. In addition, the initial position of male PN formation was predictive of the position of PN juxtaposition. It was also observed that nucleolar precursor bodies (NPBs) aligned along the juxtaposition area and this happened considerably earlier for the female PN (8.2 ± 2.6 vs.11.2 ± 4.1 h, P = 0.0001). Although it occurred rarely, displacement of juxtaposed PN to the cortex was strongly associated ( P < 0.0001) with direct cleavage into three blastomeres at the first cell division. The times of PN breakdown and first cleavage showed a very consistent trend, occurring earlier or progressively later depending on whether initial male PN positioning was central, intermediate or cortical, respectively. Finally, time intervals between discrete fertilization events were strongly associated with embryo quality on Day 3. For example, longer intervals between disappearance of the cytoplasmic halo and PN breakdown were highly predictive of reduced blastomere number and increased fragmentation ( P = 0.0001). LARGE SCALE DATA: N/A LIMITATIONS, REASON FOR CAUTION: Some of the morphokinetic parameters assessed in this study may require better definition to reduce inter-operator annotation variability. WIDER IMPLICATIONS OF THE FINDINGS: To our knowledge, overall, these data represent the most detailed morphokinetic description of human fertilization. Many of the illustrated parameters are novel and may be amenable to further elaboration into algorithms able to predict embryo quality, as suggested by the findings presented in this study. STUDY FUNDING/COMPETING INTERESTS: None.